An absolute continuity for positive operators on Banach lattices. (1991) - Feldman, W.; Piston, C.; Piston, Calvin E.
Abstract : For positive operators on a Banach lattice, absolute contnuity conditions are considered. An operator absolutely continuous with respect toT is compared to sums of compositions ofT together with orthomorphisms or in special cases projections. Consequences For compact operators on functions spacesC ( X ) are considered.